Adaptación y resiliencia al ingreso en estudiantes de Primeros semestres de la Universidad Antonio Nariño - Varon Herrera, Julian David; Lozada Lara, Yesli Paola (Universidad Antonio Nariño, 2023)
The present study was carried out with the purpose of knowing the levels of resilience and adaptation before the entrance to the university life of the students of the careers of psychology and commerce of the university Antonio Nariño, as well as the intervening factors in these levels. It was developed under the descriptive and quantitative methodology, by means of the application of two tests the IAC and the RS, processing the information statistically by means of the SPSS program with the purpose of correlating the two studied variables, for which it helped to conclude that the evaluated students of both university careers obtained significant levels of resilience as well as adaptation, showing an optimal state to face stressful situations in an adequate way, in which the personal, educational, social and family environment intervenes to continue advancing the professional training in the careers under study and in the university institution.